(NoBU^ENIE ANALIZU PO\TI^ESKOGO TEKSTAs (NmETODIKAs - (NkAGANOWT^(B.(Ns(B.(Nl(B.s ((NmOSKWAs (NrUSSKOE SLOWOs, 2007)
(NpOSOBIE POSWQ]ENO PROBLEMAM OBU^ENIQ [KOLXNIKOW (B5-11 (NKLASSOW INTERPRETACII PO\TI^ESKOGO TEKSTA(B.s
Keywords: (NmETODIKAs